Theory of Mind in Schizophirena from the Perspective of the Phenomenological Philosophical Tradition - Jerotić, Stefan (Engrami, 2025)
Human consciousness is "anchored" in the body (embodied). At the same time, humans are social beings. In the language of the phenomenological philosophical tradition, we are "immersed" in relationships with others. Accordingly, our understanding of other people's feelings is not solely a result of internal cognitive processes. Instead, we experience others' feelings through a shared, bodily-mediated experience of the world.Reconceptualizing empathy as a bodily phenomenon and recognizing the role of interaffectivity in mediating social interactions provides a new direction for understanding empathy in individuals with schizophrenia. Such an approach enables a richer and more nuanced interpretation that integrates both cognitive and bodily dimensions of human experience, opening possibilities for more effective interventions and improvement of social functioning in individuals with schizophrenia.
Keywords: Schizophrenia; Phenomenology; Theory of mind; Social cognition